New targets in the search for preventive and therapeutic agents for botulism. Issue 9 (September 2014) - Anniballi, Fabrizio; Lonati, Davide; Fiore, Alfonsina; Auricchio, Bruna; De Medici, Dario; Locatelli, Carlo Alessandro
<x xml:space="preserve">Abstract</x> Botulism is a severe neuroparalytic disease resulting from exposure to one of the most poisonous toxins to humans. Because of this high potency and the use of toxins as biological weapons, botulism is a public health concern and each case represents an emergency. Current therapy involves respiratory supportive care and anti-toxins administration. As a preventive measure, vaccination against toxins represents an effective strategy but is undesirable due the rarity of botulism and the effectiveness of toxins in treating several neuromuscular disorders. This paper summarizes the current issues in botulism treatment and prevention, highlighting the challenge for future researches.